Kajian Kapasitas Momen dengan Variasi Letak Tulangan Tarik pada Beton Kondisi Under Reinforment, Balance, Over Reinforment Menggunakan Software Abaqus - Harefa, Hartono Putera; Tarigan, Ing Johannes; Nursyamsi , Nursyamsi (Syntax Corporation, 2026)
This study evaluates the impact of tensile reinforcement placement variations on nominal moment capacity, deformation, and crack patterns of reinforced concrete blocks. Using blocks measuring 300 mm × 600 mm with concrete quality f'c = 25 MPa and steel quality fy = 400-550 MPa, the study was conducted on three conditions: under reinforced, balance, and over reinforced. The methodology includes manual analysis based on SNI 2847:2019 and numerical simulation using ABAQUS CAE with a Concrete Damage Plasticity (CDP) approach. Variations focus on the location of the tensile reinforcement without changing the reinforcement ratio or cross-sectional dimensions. Research Results: Under Reinforced: Nominal moment capacity (Mn) ranges from 264.43-275.84 kNm with an increase of 4.31%. Exhibits greater maximum deflection and more flexible collapse with gradual tensile crack initiation. Balance: There is a balance between the compressed concrete strain (εc = 0.003) and the tensile steel yield strain (εy), resulting in optimal bending performance with an increase in Mn of 9.48%. Over Reinforced: Significant moment capacity increase (1164.04-1277.51 kNm) with an increase of 9.75%, but experienced brittle and brittle concrete compressive collapse with smaller deflection. Conclusion: Variations in tensile reinforcement placement, although the reinforcement ratio remains the same, have a significant effect on the moment capacity and collapse mechanism. The over reinforced condition, although it produces the highest strength, is less recommended for structures that require high ductility due to the nature of sudden collapse. These findings can be the basis for optimizing the design of flexible reinforcement to improve the safety and performance of reinforced concrete structures.